Population Density of Damselfly Agriocnemis femina (Odonata: Coenagrionidae) in Manik Rambung Ricefield, Simalungun-Sumatera Utara - Ameilia Zuliyanti Siregar; Che Salmah Md. Rawi; Zulkifli Nasution (Jurnal Ilmu Pertanian KULTIVAR, 2011)
The objective of this research was to study effect and correlation of physics-chemistries with density of A. femina. The method using Mark Release Recapture with 8 stations in Manik Rambung Village, Simalungun District. The result showed 2351 individuals of A. femina, consist of male 1345 individuals and female 1006 individuals. Comparison of male and female were 87% and 13%, while score of Lincoln’s indices highest calculated in twelve sampling were 451 individuals. The result of analysis correlation showed humidity given effects on population of density A. femina recapture were 0.432. Keyswords : Density, damselfly, Agriocnemis femina, rice field, Simalungun.